HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN PENERIMAAN DIRI PADA REMAJA DI PONDOK PESANTREN AL-ISLAM KABUPATEN GORONTALO - Muhamad Mursyid; Riskawati Ladiku (Elsia: Jurnal Psikologi Manusia, 2023)
Adolescents who live in Islamic Boarding Schools are prone to experiencing self-acceptance problems. The ability to accept one’s self can be influenced by one of their social support. The study aims to determine the relationship between social support and self-acceptance in adolescents at Al Islam Islamic Boarding School, Gorontalo Regency. Quantitative research with a cross-sectional study approach. The independent variable is social support, while the dependent variable is self-acceptance. The population is adolescents in seventh grade with as many as 228 people. The sample was 45 people with a purposive sampling technique. Data were collected by questionnaire and analyzed using product moment and linearity tests. The results showed that adolescents at Al-Islam Islamic Boarding School mostly had moderate social support (62.2%) and moderate self-acceptance (57.8%). The results of the analysis obtained a significance value (ρ) of 0.001, an F deviation from linearity value of 1.096, and a p-value of 0.403 (>0.05). It is concluded that there is a relationship between social support and adolescent self-acceptance at Al-Islam Islamic Boarding School, Gorontalo Regency.